2007
DOI: 10.1111/j.1365-2966.2007.11885.x
|View full text |Cite
|
Sign up to set email alerts
|

Close encounters in young stellar clusters: implications for planetary systems in the solar neighbourhood

Abstract: The stars that populate the solar neighbourhood were formed in stellar clusters. Through Nbody simulations of these clusters, we measure the rate of close encounters between stars. By monitoring the interaction histories of each star, we investigate the singleton fraction in the solar neighbourhood. A singleton is a star which formed as a single star, has never experienced any close encounters with other stars or binaries, or undergone an exchange encounter with a binary. We find that, of the stars which forme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
140
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(140 citation statements)
references
References 39 publications
0
140
0
Order By: Relevance
“…Moreover, most stars form in embedded cluster environments (Lada & Lada 2003) where dynamical evolution can lead to the acquisition of transient companions (Malmberg et al 2007). Recently, Batygin (2012) showed that the presence of a companion to a young star can force the proto-planetary disk to precess around the binary's axis, so that the plane in which planets eventually form and the equatorial plane of the central star can differ.…”
Section: Disk Torquingmentioning
confidence: 99%
“…Moreover, most stars form in embedded cluster environments (Lada & Lada 2003) where dynamical evolution can lead to the acquisition of transient companions (Malmberg et al 2007). Recently, Batygin (2012) showed that the presence of a companion to a young star can force the proto-planetary disk to precess around the binary's axis, so that the plane in which planets eventually form and the equatorial plane of the central star can differ.…”
Section: Disk Torquingmentioning
confidence: 99%
“…At the same time, the orbital elements of the planet are changed on a short timescale. A sudden jump occurs in both eccentricity and semimajor axis, as predicted by Malmberg et al (2011Malmberg et al ( , 2007, Davies (2009), andZakamska &Tremaine (2004).…”
Section: Case A: a Single Planet Orbiting At 18 Au From The Starmentioning
confidence: 84%
“…In effect, most numerical modeling of the effects of stellar encounters on planetary systems in clusters are based on pure N-body simulations where the effects of circumstellar disks are neglected (Malmberg et al 2011(Malmberg et al , 2007Malmberg & Davies 2009;Zakamska & Tremaine 2004). However, as suggested by the near coincidence between the cluster lifetime and that of circumstellar disks, this assumption may not be fully justified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stellar flybys have been invoked to explain the high eccentricity orbits of some Kuiper belt objects such as Sedna (Kenyon & Bromley 2004), the dynamics of planetary systems (Malmberg et al 2007;Spurzem et al 2009), and the structures of debris disks (Larwood 1997;Mouillet et al 1997;Kalas et al 2000;Kobayashi & Ida 2001). Impacts of stellar flybys during A&A 532, A120 (2011) the first few million years have also been studied in the context of the evolution of protoplanetary disks and planet formation (Bonnell et al 2001;Olczack et al 2009).…”
Section: Introductionmentioning
confidence: 99%